Efisiensi Pemasaran Sapi Potong di Kecamatan Takisung Kabupaten Tanah Laut Provinsi Kalimantan Selatan - Yusuf Azis; Ibnu Husin (University of Islam Malang, 2021)
Takisung District is one of the centers for beef cattle in Tanah Laut Regency. In creating an efficient and profitable marketing system for both farmers and consumers, farmers must choose short marketing channels. This study aims to identify the shape of the beef cattle marketing channel, determine the costs, benefits, margins, and farmer's share, and the marketing efficiency received by beef cattle producers. This research was conducted in Takisung District, Tanah Laut Regency. The sample villages were chosen deliberately, namely the three villages with the highest number of farmers (Source Makmur Village, Takisung Village, and Gunung Makmur Village). The sample of farmer respondents in each village was chosen randomly in proportion, with a total sample of 30 farmers. To select local traders and cutting traders, the snowball sampling method was used. The study was conducted from March to May 2020. The results showed that there were 4 forms of beef cattle marketing channels, namely Channel I (breeders – consumers), Channel II (breeders – slaughterers-consumers), Channel III (breeders – local traders – consumers), and Channel IV (breeders – local traders – slaughterers – consumers). Furthermore, costs, profits, margins, and farmer's share per head of cattle as well as marketing efficiency for each marketing channel, namely channel 1 with costs, profits, and marketing margins of Rp.0 and farmer's share get 100% results. Channel 2 with a cost of Rp. 570,000, a profit of Rp. 4,950,000 and a margin of Rp. 5,520,000 and a farmer's share with a yield of 73.74%. Furthermore, channel 3 with a cost of Rp.243,000, a profit of Rp.457,000, and a margin of Rp.700,000, and farmer's share obtained a yield of 95.39%. Finally, channel 4 with a cost of Rp. 1,766,000, a profit of Rp. 5,124,000 and a margin of Rp. 5,920,000 and farmer's share getting 71.84% results. Economically, beef cattle marketing can be said to be relatively efficient in all marketing channels. The most efficient marketing channels are channel 1 and channel 3.